2010
DOI: 10.2422/2036-2145.2010.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Compact moduli for certain Kodaira fibrations

Abstract: We explicitly describe the possible degenerations of a class of double Kodaira fibrations in the moduli space of stable surfaces. Using deformation theory we also show that under some assumptions we get a connected component of the moduli space of stable surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Using these explicit descriptions Rollenske went further in [Rol10] and showed that, in the case where the branched cover has a cyclic Galois group, then the closure of this irreducible component inside the Kollár-Shepherd Barron-Alexeev [K-SB88] compactification is again a connected component. One should observe that there are extremely few examples where the connected components of the KSBA compact moduli space have been investigated, apart from the obvious case of rigid surfaces (see [LW12] for the case of surfaces isogenous to a product).…”
Section: And Siu [M-s80]mentioning
confidence: 99%
“…Using these explicit descriptions Rollenske went further in [Rol10] and showed that, in the case where the branched cover has a cyclic Galois group, then the closure of this irreducible component inside the Kollár-Shepherd Barron-Alexeev [K-SB88] compactification is again a connected component. One should observe that there are extremely few examples where the connected components of the KSBA compact moduli space have been investigated, apart from the obvious case of rigid surfaces (see [LW12] for the case of surfaces isogenous to a product).…”
Section: And Siu [M-s80]mentioning
confidence: 99%
“…An explicit study of compactifications of the moduli spaces of surfaces of general type was pursued in [VanOp06], [Al-Par09], [LW10], [Rol10].…”
Section: Smoothings and Surgeriesmentioning
confidence: 99%
“…Although M h shares many nice properties of M g , e.g., it is a DM-stack of finite type over the base field, it may possibly have many connected components that behave very differently [Cat86,Vak06]. Hence, almost all available results on the global geometry of M h pertain to specific components of the moduli of surfaces (e.g., [vO05,vO06,Liu12,Rol10,AP09,Lee00]) or special components of the moduli of log-stable varieties (e.g., [HKT06,HKT09,Ale02,Has99,Hac04]).…”
Section: Introductionmentioning
confidence: 99%